2010
DOI: 10.1002/pssc.201000039
|View full text |Cite
|
Sign up to set email alerts
|

Study of macroporous silicon electrochemical etching in 3D structured N type silicon substrates

Abstract: In this paper, the electrochemical etching of 3D n‐type substrates is investigated. These types of 3D structures are of interest to increase the active surface of some systems. Our aim is to improve a MEMS (Micro‐Electro Mechanical System) micro fuel cell power through total surface enhancement without any modification of the cell footprint. To reach this objective, we perform a gas diffusion layer using localized macro‐porous silicon. The porous area total surface is improved through trench formation (before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…It was demonstrated in previous work that it is possible to perform conformal PS layers even on textured surfaces. 22 In fact, in the case of highly doped silicon, the holes that are required for the electrochemical reaction (see PS formation Equation 1 from Ref. 24) equation are provided near the silicon surface by means of tunneling effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated in previous work that it is possible to perform conformal PS layers even on textured surfaces. 22 In fact, in the case of highly doped silicon, the holes that are required for the electrochemical reaction (see PS formation Equation 1 from Ref. 24) equation are provided near the silicon surface by means of tunneling effects.…”
Section: Resultsmentioning
confidence: 99%
“…Previous study has shown that a high silicon surface doping level is essential for achieving conformal PS formation. 22 Therefore, low-resistivity (1 m .cm) silicon wafers were used in this work for simple experimental demonstration. For normal-resistivity (10-30 .cm) substrates, a step of diffusion doping and drive-in should be added before the anodization.…”
Section: Device Design and Fabrication Processmentioning
confidence: 99%
“…Afterwards, subsequent PS etching in a 30% HF mixture with acetic acid as wetting agent (in potentiostatic conditions at 3.1 V) was performed to produce macro‐PS. It permits to perform porous 3D structures that are presented in Figure . This picture shows a structure partially porous with 30% of the total surface presenting pores going through the silicon substrate to perform the flow channel function.…”
Section: Integration Of Porous Silicon In Small‐size Fuel Cellsmentioning
confidence: 99%
“…Structure observed after single‐side alkaline etching and an anodization under potentiostatic conditions at 3.1 V during 4 h in a HF 30%–acetic acid–water electrolyte, after .…”
Section: Integration Of Porous Silicon In Small‐size Fuel Cellsmentioning
confidence: 99%
See 1 more Smart Citation